ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CORPORATE SOCIAL RESPONSIBILITY DISCLOUSURE (CSRD): STUDI PADA PERUSAHAAN MANUFAKTUR TAHUN 2017-2019 - Nurcahyono nurcahyono (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This study aims to test empirically the factors that influence corporate social responsibility disclosure (CSRD). The predictor variables used are Company Size, Profitability, Dept to Equity Ratio (DER) and Net Profit Margin (NPM). The research population is manufacturing companies listed on the IDX from 2017 to 2019, the sampling method used is purposive sampling. Analysis of research data using multiple linear regression and data testing using SPSS-23 software. The research sample according to the sampling criteria is 34 companies, so that the observations are 102 firm years. The results showed that company size, profitability and NPM had a positive effect on corporate social responsibility disclosure (CSRD) and DER had a negative effect on corporate social responsibility disclosure (CSRD). Overall the independent variables used have an influence on CSRD, based on the t test the independent variable affects 33.6% while 66.4 is influenced by other variables not used in this study. The implication of this research is that CSRD can be increased by increasing company size, profitability and NMP and reducing DER. Keywords: CSRD, Company Size, Profitability, DER and NPM.